Spectroscopic and Chromatographic Estimation of Some Sartans and their Combinations with Thiazide Diuretics: A Review - Baviskar, Kajal P.; Kachave, Ramanlal N. (Current Pharmaceutical Analysis, 2023)
Sartans are often used as antihypertensives. They are also available in combination with thiazide diuretics for the management of hypertension. Analytical method development is a crucial part of successful drug development and characterization. Bioanalytical studies are of paramount importance while establishing pharmacokinetic and toxicokinetic data while forced degradation studies are important to elucidate degradation pathways and to establish stability of the drugs.Different methods have been developed for the analysis of sartans and their combination with thiazide diuretics. We thought it imperative to summarize them so the data could be useful for analysis of newer sartans. The review describes various methods for analysis of some frequently employed sartans as well as the latest sartans and their combination with thiazide diuretics. The article also focuses on their analysis of biological fluids. Forced degradation studies have also been covered in the article.Article is divided into three sections. First section covers introduction, second section focuses on different methods developed, including bioanalytical methods, while third section presents forced degradation studies carried out on the drugs. Important parameters of the analytical methods developed have been summarized in tabular form.
Keywords: thermal stress